Determination of the informative components of the validity of the reactive maneuverability of the motor potential of a fencer by the «information compression» method - Pugachev, I.Yu.; Ponomarev, G.N.; Rodichkin, P.V.; Kostov, F.F. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the integrative latent indicators of the validity of the reactive maneuverability of the fencers' motor potential. Methods and structure of the study. The respondents were junior fencers aged 18-21, who train at the Children's and Youth Sports School of the Michurinsky district of Tambov (n=12). At the first stage of the work, parameters were studied that directly or indirectly influence the reactive maneuverability of the fencers' motor potential. At the second stage, a two-dimensional biometric analysis was performed using the paired Bravais-Pearson correlation coefficient (r). At the third stage of the work, the degree of significance of the indicators revealed by the two-dimensional mathematical and biometric analysis, which probabilistically affect the reactive maneuverability of the fencers' motor potential, was verified. Result and conclusions. Integrative indicators of the validity of the latent reactive maneuverability of the fencer's motor potential as an important prognostic feature were established, namely: the search time for the motor unit, the coefficient of accuracy of the motor unit control, the average latent time according to the "tapping test" method, the duration of the potential of the motor unit of the biceps muscle of the shoulder, the speed propagation of excitation along the radial nerve.